Methodological Aspects of μLC-MS/MS for Wide-Scale Proteomic Analysis of Anthracycline-Induced Cardiomyopathy - Kupčík, Rudolf; Lenčová, Olga; Mazurová, Yvona; Štěrba, Martin; Vajrychová, Marie (ACS omega, 2025)
The efforts to utilize microflow liquid chromatography hyphenated to tandem mass spectrometry (μLC-MS/MS) for deep-scale proteomic analysis are still growing. In this work, two-dimensional LC separation and peptide derivatization by a tandem mass tag (TMT) were used to assess the capability of μLC-MS/MS to reveal protein changes associated with the severe chronic anthracycline cardiotoxicity phenotype in comparison with nanoflow liquid chromatography (nLC-MS/MS). The analysis of the control and anthracycline-treated rabbit myocardium by μLC-MS/MS and nLC-MS/MS allowed quantification of 3956 and 4549 proteins, respectively, with 84% of these proteins shared in both data sets. Both nLC-MS/MS and μLC-MS/MS revealed marked global proteome dysregulation in severe anthracycline cardiotoxicity, with a significant change in approximately 55% of all detected proteins. The μLC-MS/MS analysis allowed less compressed and more precise determination of the TMT channel ratio and correspondingly broader fold-change protein distribution than nLC-MS/MS. The total number of significantly changed proteins was higher in nLC-MS/MS (2498 vs 2183, 1900 proteins shared), whereas the opposite was true for a number of significantly changed proteins with a fold-change cutoff ≥ 2 (535 vs 820). The profound changes concerned mainly proteins of cardiomyocyte sarcomeres, costameres, intercalated discs, mitochondria, and extracellular matrix. In addition, distinct alterations in immune and defense response were found with a remarkable involvement of type I interferon signaling that has been recently hypothesized to be essential for anthracycline cardiotoxicity pathogenesis. Hence, μLC-MS/MS was found to be a sound alternative to nLC-MS/MS that can be useful for comprehensive mapping of global myocardial proteome alterations such as those associated with severe anthracycline cardiotoxicity.